Spider-girl. - DeFalco, Tom (Marvel Comics, 2005)
The adventures of Spider-Man's daughter continue as Mayday once again faces Kaine, Spider-Man swings again, and Darkdevil is... actually nice?! Plus: Meet new heroes and villains, take a peek into the fantasies of Mayday's friends, and witness the return of the Green Goblin!